Dental impact of anti-fibroblast growth factor 23 therapy in X-linked hypophosphatemia - Elis J. Lira dos Santos; Kenta Nakajima; Julien Po; Ayako Hanai; Volha Zhukouskaya; Martin Biosse Duplan; Agnès Linglart; Takashi Shimada; Catherine Chaussain; Claire Bardet (Nature Publishing Group, 2023)
Abstract Elevated fibroblast growth factor 23 (FGF23) in X-linked hypophosphatemia (XLH) results in rickets and phosphate wasting, manifesting by severe bone and dental abnormalities. Burosumab, a FGF23-neutralizing antibody, an alternative to conventional treatment (phosphorus and active vitamin D analogs), showed significant improvement in the long bone phenotype. Here, we examined whether FGF23 antibody (FGF23-mAb) also improved the dentoalveolar features associated with XLH. Four-week-old male Hyp mice were injected weekly with 4 or 16 mg·kg−1 of FGF23-mAb for 2 months and compared to wild-type (WT) and vehicle (PBS) treated Hyp mice (n = 3-7 mice). Micro-CT analyses showed that both doses of FGF23-mAb restored dentin/cementum volume and corrected the enlarged pulp volume in Hyp mice, the higher concentration resulting in a rescue similar to WT levels. FGF23-mAb treatment also improved alveolar bone volume fraction and mineral density compared to vehicle-treated ones. Histology revealed improved mineralization of the dentoalveolar tissues, with a decreased amount of osteoid, predentin and cementoid. Better periodontal ligament attachment was also observed, evidenced by restoration of the acellular cementum. These preclinical data were consistent with the retrospective analysis of two patients with XLH showing that burosumab treatment improved oral features. Taken together, our data show that the dentoalveolar tissues are greatly improved by FGF23-mAb treatment, heralding its benefit in clinics for dental abnormalities.